Inside the RAMP–Accelerate Bootcamp and Venture Showcase - Steele, Megan (2025)
The recent RAMP–Accelerate Bootcamp and Venture Showcase, hosted in Palmira, Colombia, marked a pivotal moment in the journey of nine science-backed ventures—each born from Alliance research and primed to move toward real-world impact. Read on about this milestone event to ensure that promising agri-food science-based innovations don’t remain on the shelf but create real, tangible value for people and the planet, and how to get involved for the next steps.